The hypoxic tissue microenvironment as a driver of mucosal inflammatory resolution - Cartwright, Ian M.; Colgan, Sean P. (Frontiers in Immunology, 2023)
On the backdrop of all acute inflammatory processes lies the activation of the resolution response. Recent years have witnessed an emerging interest in defining molecular factors that influence the resolution of inflammation. A keystone feature of the mucosal inflammatory microenvironment is hypoxia. The gastrointestinal tract, particularly the colon, exists in a state of physiological hypoxia and during active inflammation, this hypoxic state is enhanced as a result of infiltrating leukocyte oxygen consumption and the activation of oxygen consuming enzymes. Most evidence suggests that mucosal hypoxia promotes the active resolution of inflammation through a variety of mechanisms, including extracellular acidification, purine biosynthesis/salvage, the generation of specialized pro-resolving lipid mediators (ie. resolvins) and altered chemokine/cytokine expression. It is now appreciated that infiltrating innate immune cells (neutrophils, eosinophils, macrophages) have an important role in molding the tissue microenvironment to program an active resolution response. Structural or functional dysregulation of this inflammatory microenvironment can result in the loss of tissue homeostasis and ultimately progression toward chronicity. In this review, we will discuss how inflammatory hypoxia drives mucosal inflammatory resolution and its impact on other microenvironmental factors that influence resolution.